2013
DOI: 10.1037/a0034084
|View full text |Cite
|
Sign up to set email alerts
|

What you read matters: The role of fiction genre in predicting interpersonal sensitivity.

Abstract: Previous studies have found a positive relationship between exposure to fiction and interpersonal sensitivity. However, it is unclear whether exposure to different genres of fiction may be differentially related to these outcomes for readers. The current study investigated the role of four fiction genres (i.e., Domestic Fiction, Romance, Science-Fiction/Fantasy, and Suspense/Thriller) in the relationship between fiction and interpersonal sensitivity, controlling for other individual differences. Participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 38 publications
9
97
4
2
Order By: Relevance
“…Although we found no experimental effect of reading material on performance on the Intuitive Physics Test, our correlational results suggest that the relationship between lifelong reading habits and ToM ability (Kidd & Castano, 2013;Fong et al, 2013;Mar et al, 2006;Mar, Oatley, et al, 2009;Mar, Tackett, et al, 2009) may extend to non-social cognitive ability. Scores on the ART were the strongest predictor of RME performance in our study, as had been the case for Kidd and Castano (v p 2 = .13 in our study and theirs; for IP, the effect was v p 2 = .12).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Although we found no experimental effect of reading material on performance on the Intuitive Physics Test, our correlational results suggest that the relationship between lifelong reading habits and ToM ability (Kidd & Castano, 2013;Fong et al, 2013;Mar et al, 2006;Mar, Oatley, et al, 2009;Mar, Tackett, et al, 2009) may extend to non-social cognitive ability. Scores on the ART were the strongest predictor of RME performance in our study, as had been the case for Kidd and Castano (v p 2 = .13 in our study and theirs; for IP, the effect was v p 2 = .12).…”
Section: Discussioncontrasting
confidence: 58%
“…Although our results support past experimental (Kidd & Castano, 2013) and correlational (Fong et al, 2013;Mar et al, 2006;Mar, Oatley, et al, 2009;Mar, Tackett, et al, 2009) research, the current study has a variety of limitations, many of which can be attributed to the use of a within-subject design. Many participants were unwilling or unable to read four separate pieces over a three-hour period, even with breaks, and we had to discard one third of the original sample.…”
Section: Limitations and Suggestions For Future Researchcontrasting
confidence: 63%
See 2 more Smart Citations
“…Stories entail the actions and experiences of one or more protagonists and a plot line with certain schematic elements (e.g., setting, event, attempt, reaction, and consequence; Rumelhart, 1975). In recent years, empirical research has demonstrated that fictional as well as nonfictional narratives can have a pervasive impact on attitudes and beliefs about real-world issues (narrative persuasion; e.g., Green & Brock, 2000; Prentice et al, 1997), on knowledge and memory (Fazio & Marsh, 2008; Marsh, Meade, & Roediger, 2003), and on social abilities and personality (Fong, Mullin, & Mar, 2013; Mar & Oatley, 2008). In some of these studies the stories as a whole or their main narrative arc suggested a particular stance toward a topic (e.g., a story about a psychiatric patient who murdered a child led recipients to have more negative beliefs about the group of psychiatric patients; Green & Brock, 2000).…”
Section: Introductionmentioning
confidence: 99%